Generalisation of availability models for resilient systems with online verification - Vyacheslav Kharchenko; Yuriy Ponochovnyi; Oleksandr Ivasiuk; Oleg Illiashenko; Olena Ponochovna (International Journal of Electronics and Telecommunications)
This paper analyses online verification methods for safety- and security-critical systems, including aerospace, nuclear instrumentation, and smart home systems. It emphasizes the need for resilience and adaptability in these systems to withstand various environmental conditions and potential threats. Several Markov models are developed to evaluate the dependability of control systems for small modular reactors. These models illustrate how online verification, by enabling early detection of failures, can enhance resilience and improve system performance. The findings suggest that optimising verification parameters is crucial for this enhancement, providing a foundation for future research in critical control systems.